Análisis de requerimientos y requisitos funcionales del sistema de información utilizado en la microempresa Pcmovil soluciones s.a. de la parroquia san juan del cantón Puebloviejo. - Moran Romero, Carlos Gabriel (2024)
In the present study, the analysis of requirements and functional requirements of the information system used in the microenterprise Pcmovil Solutions S.A. was carried out exhaustively. of the San Juan Parish of the Puebloviejo Canton. The main objective of executing this study was to analyze this system in detail from different perspectives, applying various research techniques with the purpose of identifying possible areas of improvement and thus propose several strategies that allow improving the operational management of the microenterprise. The basis of the research carried out is based on the need to optimize internal business processes, ensuring effective information management and full adaptation to the dynamics of the mobile solutions market, characterized by its constant development. It is of great importance to highlight the analysis of the needs and functional requirements which will allow us to provide improvements that directly affect the quality of the service offered and, however, customer satisfaction, which is a key element for the success of the microenterprise. . Likewise, to carry out this research, two interviews were applied, one of them was directed to the person in charge of the Technical Area, while the other was conducted to the Manager of the microenterprise. The implementation of these interviews revealed the great commitment that the micro-enterprise Pcmovil Solutions S.A. has. to promote and provide effective service to its clients. Therefore, this research carried out not only allowed us to analyze the requirements and functional requirements in the information system, but also proposed several perspectives to be able to make the corresponding improvements in the microenterprise.